Rancang Bangun Sistem Informasi Pemagang Indonesia Berbasis Web Menggunakan Framework Laravel: (Studi Pada Prefektur Ibaraki, Jepang) (Elkom: Jurnal Elektronika dan Komputer, 2026)
Abstract—Japan is one of the main destinations for Indonesian migrant workers participating in internship programs. Ibaraki Prefecture, particularly Kitaibaraki City, hosts many Indonesian interns in the fisheries, agriculture, manufacturing, and construction sectprocesses, customer data recording, trip scheduling, and report preparation manually through WhatsApp and separate worksheets, resulting in problems such as uncentralized data, risk of recording errors, and difficulties in schedule management.This study aims to develop an information website for Indonesian interns in Ibaraki Prefecture, Japan. The website provides information on pre-departure preparation, daily life, rights and obligations, cultural adaptation, local communities, and practical experiences from former and current interns. It is expected to serve as an educational platform, a reliable source of information, and a communication bridge between prospective interns, active interns, alumni, and families in Indonesia. Ultimately, the website is expected to improve the preparedness and well-being of Indonesian interns while strengthening the positive image of the Indonesian community in Japan